Talking About Hepatitis C: FAQs From Young Adults Who Inject Drugs. Issue 6 (November 2018) - Knight, Lauren L.; Wagner, Katherine; Leyva, Yuridia; Bruce, Veronica R.; White, Kirsten A. M.; Talamantes, Yvonne S.; Price, Brittany; Page, Kimberly; Carvour, Martha L.
Introduction . Young adults who inject drugs and live in rural communities are at high risk for hepatitis C virus (HCV) infection. Recent changes in HCV treatment must be communicated within these communities to improve access to care and reduce HCV transmission. Methods . Field workers in the ¡VÁLE! Hepatitis Treatment and Integrated Prevention Services study identified frequently asked questions (FAQs) posed by young-adult participants at high risk for HCV during screening and educational sessions. From 2016 to 2018, 183 young adults (44.3% women; 85.8% Latino/a) younger than 30 years who inject drugs and reside in Rio Arriba or Doña Ana counties in New Mexico were enrolled. The research team compiled deidentified questions during field enrollments. Results . FAQs were reviewed and categorized into four major domains, including risk/prevention, screening, treatment, and reinfection. FAQs were addressed by a team of medical and public health professionals, using the most current research and recommendations. Conclusions . These FAQs address important gaps in HCV knowledge among young adults who are at high risk for infection. The FAQs also highlight the importance of risk reduction counseling provided by frontline public health providers as well as access to safe and effective HCV treatments for young adults who inject drugs.